EXPRESSIVE MEANS AND STYLISTIC DEVICE - Sulaymonov Samariddin; Iskandarov Hayotbek; Abdurakhmanova Zilola (Ta’lim innovatsiyasi va integratsiyasi, 2023)
Annotatsiya Stylistic devices refer to any of a variety of techniques to give an additional and/or supplemental meaning, idea, or feeling. Also known as figures of speech or rhetorical devices, the goal of these techniques is to create imagery, emphasis, or clarity within a text in hopes of engaging the reader.